Factors influencing intentions to use Apple Pay: A behavioral perspective - Khalid Waleed Abdo; Imdadullah Hidayat-ur-Rehman; Sultan Bader Aljehani; Esam Mohammed Aloufi; Ali Alshehri (PLoS ONE, 2025)
The study aims to investigate factors influencing Apple Pay adoption, focusing on lifestyle congruence, perceived security, perceived trust, perceived financial control, ease of use, and relative advantage. By applying the Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI) theory, it seeks to understand these factors’ contributions to user perception and adoption, providing insights into user behavior and enhancing the effectiveness of digital payment solutions. A survey approach was employed, combining stratified random sampling and convenience sampling to collect data from major cities in Saudi Arabia, targeting Apple-pay users. The survey was distributed online via social media platforms. Data from 221 valid responses were analyzed using partial least squares structural equation modeling. The study revealed that the model explains 62.2% of the variance in the intention to use Apple Pay. Key findings include significant impacts of perceived financial control, relative advantage, perceived security, perceived trust, and ease of use on the intention to use Apple Pay. Lifestyle congruence and ease of use influenced usage intentions but not perceived relative advantage. These results underscore the importance of security, trust, and ease of use in driving Apple Pay adoption. The multi-group analysis findings indicate that younger users prioritize security and lifestyle congruence, while females value financial control and lifestyle fit, and males emphasize security and trust in their Apple Pay adoption decisions. This study uniquely integrates the DOI theory and TAM to examine Apple Pay adoption, highlighting the critical roles of perceived financial control, security, and trust. It expands traditional TAM by incorporating financial control, emphasizes security’s impact on trust, and introduces lifestyle congruence as a significant adoption driver. This comprehensive framework provides valuable insights for digital payment adoption.